Nociceptive Pain: Current Updates In Mechanisms And Pathway. - GURUDEV SINGH RAINA; ARACHNA KHURANA; MANOJ SONI (International Journal of Pharma and Bio Sciences, 2011)
Pain is a fundamental experience with a complex and multilayered neurobiological basis. The sensation of pain alerts us to real or impending injury and triggers appropriate protective responses. Unfortunately, pain often outlives its usefulness as a warning system and instead becomes chronic and debilitating. Pain is usually elicited by the activation of specific nociceptors (`nociceptive pain’). However, it may also result from injury to sensory fibres, or from damage to the CNS itself (`neuropathic pain’). In recent years a powerful battery of techniques has been brought to bear to unravel the mechanisms by which painful stimuli are transduced and processed. There have been several recent discoveries regarding the molecular transduction mechanisms in nociceptors and novel molecular and cellular mechanisms underlying the spinal processing of painful stimuli. The highly disagreeable sensation of pain results from an extraordinarily complex and interactive series of mechanisms integrated at all levels of the neuroaxis, from the periphery, via the dorsal horn to higher cerebral structures. In addition to familiar inflammatory mediators, such as prostaglandins and bradykinin, potentially-important, pronociceptive roles have been proposed for a variety of `exotic’ species, including protons, ATP, cytokines, neurotrophins (growth factors) and nitric oxide. Further, both in the periphery and in the CNS, non-neuronal glial and immunecompetent cells have been shown to play a modulatory role in the response to inflammation and injury, and in processes modifying nociception. . In the dorsal horn of the spinal cord, wherein the primary processing of nociceptive information occurs, N-methyl-D- aspartate receptors are activated by glutamate released from nocisponsive afferent fibres. Their activation plays a key role in the induction of neuronal sensitization, a process underlying prolonged painful states. In addition, upon peripheral nerve injury, a reduction of inhibitory interneurone tone in the dorsal horn exacerbates sensitized states and further enhance nociception. As concerns the transfer of nociceptive information to the brain, several pathways other than the classical spinothalamic tract are of importance: for example, the postsynaptic dorsal column pathway. The rich variety of key molecular players that have emerged in physiological and pathophysiological pain states reflects the sophistication and uniqueness of this vitally important sense.